51. PRE-AND POST-VATS MEDIASTINAL LYMPH NODES ASSESSMENT OF EARLY STAGE NON-SMALL CELL LUNG CANCER AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Introdution: Non-small cell lung cancer (NSCLC) is frequently cancer and the leading cause death of cancer. Surgery is an effective treatment to the early stages. There are factors that help determine the stage, mediastinal lymph nodes play an important role so it is necessary to evaluate the characteristics of mediastinal lymph nodes and surgical results.Methods: Retrospective of Early stage NSCLC cases with mediastinal lymph node evaluation underwent lobectomy (VATS) at Thong Nhat Hospital from January 2020 to January 2024.Results: 51 patients. There are 32 males and 19 females, mean age is 59.1. There are 72.5% of patients had symptomatic disease; 100% had CT scan, 1 case had PET scan. 14 cases of lymph node dissection were seen during surgery. Before surgery: N1 lymph nodes were 11.7%, after surgery N1 lymph nodes were 11.7%, N2 lymph nodes were 11.7%.; Adenocarcinoma is 64.7%. The mean operating time is 119,2 ± 33,79 minutes. Hospitalization is 10,8 ± 02,1 days. 06 cases were converted to thoracotomy. Complications: pneumonia were 29.4%, prolonged air-leak 09.6%, pleeding 15,7% (01 case at the cut when using 1 stapler to cut 02 arteries at the same time). There is not perioperative mortality.Conclusion: Determining the stage of the disease plays a very important role in the treatment of early-stage NSCLC. The status of metastatic lymph nodes changes during surgical assessment, with 23.4% of metastatic lymph nodes detected during surgery. Video-assisted laparoscopic lobectomy gives good results.
Keywords: Non-Small Cell Lung Cancer (NSCLC); early stage; thoracoscopy surgery